Ameliorative effects of phlorotannin-rich fraction of Sargassum tenerrimum in high-fat diet and low dose streptozotocin-induced metabolic changes and oxidative stress in diabetic rats - Narasimha Kumar Godlaveti Vijay; Chitra Vellapandian (Shahrekord University of Medical Sciences, 2023)
Introduction: Type 2 diabetes mellitus (T2D) is a progressing polygenic disease demanding a multitargeted treatment strategy. Sargassum tenerrimum (ST) is a marine brown alga with potentially bioactive chemicals that could be used as innovative biotherapeutics for diabetes treatment. The current research examined the potential of the phlorotannin-rich fraction from S. tenerrimum (PST) to mitigate diabetes in Wistar albino rats induced with high-fat diet (HFD) and streptozotocin (STZ) administration. Methods: Diabetic rats were given PST (200 and 400 mg/kg) or metformin (250 mg/kg) orally three weeks, and followed by the measurements of insulin, glycemic factors, biological markers of oxidative stress, tumor necrosis factor-alpha (TNF-α), as well as hepatic and pancreatic histopathological changes. Results: PST treatment significantly decreased fasting blood glucose, insulin resistance, lipid profile, hepatic profile, and TNF- α levels and improved serum insulin and glucose tolerance in diabetic rats. In the skeletal muscles of diabetic rats, PST led to a significant rise in antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) reductase, and a decrease in lipid peroxidation. Furthermore, PST treatment significantly reduced pancreatic-cell damage and hepatic fatty accumulation. PST was more efficacious at 400 mg/kg exhibiting a dose-dependent effect. Conclusion: PST improves glucolipid metabolism in HFD and STZ-induced diabetic rats, probably by reducing hyperglycemia, insulin resistance, dyslipidemia, oxidative stress, inflammation, and damage to pancreatic and hepatic architectures. The findings suggest that PST has a curative impact on diabetes mellitus type 2 and represents a new subject of study for the treatment of diabetes naturally.